Sedimentological and malacological comparisons between the Upper Saalian and Upper Weichselian loess superimposed in the Nantois cliff (Brittany, France): Reconstruction of their environments south of the British Ice Sheet - Danukalova, Guzel; Lefort, Jean-Pierre; Monnier, Jean-Laurent; Osipova, Eugenia; Pustoc’h, François; Le Bannier, Jean-Christophe (ArchéoSciences, 2017)
The site of Nantois is located in Brittany (France), almost at the westernmost end of Europe. The outcrop consists of loam, loess and slope deposits, now continuously eroded by the sea. The layers containing fragments of rock and loam are completely decalcified. Only the loess of the lower and upper parts of the section corresponding to the Nantois (Middle Pleistocene) and Sables-d’Or-Les-Pins (Late Pleistocene) formations are well preserved and display mollusc shells. A detailed study of the sediment and of the fauna permitted to better characterize the two loess. The older loess is characterized by a large variety of species. The analysis of their distribution indicates for the first time the existence of three moderate climatic improvements during the sedimentation. The lower part of the younger loess is poor in mollusc shells which are either absent or only exist as single finds or detritus, above, the molluscs composition indicates cold and severe climatic conditions during the sedimentation and can be correlated with the last glacial stage MIS 2. According to geochronological data, the upper part of the Nantois Formation corresponds to the glacial stage MIS 6. The origin of the discrepancies observed in the evolutions of the two loess was probably not related with the small difference in their distances respect with the Weichselian and Saalian British ice sheets but to the very different durations of the Upper Saalian (60 ka) and Upper Weischelian (7 ka) loess depositions. The absence of any significant warming episode during the Upper Weischelian and the existence of three climatic improvements during the Upper Saalian support the concept of sub-Milankovitch cycles which suggests that we cannot have any climatic change during a period shorter than 11Ka. Le site de Nantois est situé en Bretagne (France), presque à l’extrémité la plus orientale de l’Europe. L’affleurement est constitué de limons, de loess et de dépôts de pente maintenant régulièrement érodés par la mer. Les niveaux contenant des fragments ...